Does Decentralization Matter in Health Outcomes? Evidence from 22 OECD Unbalanced Panel Data for 1995-2005 - Kang, Youngju; Cho, Wonhyuk; Jung, Kwangho (International review of public administration, 2012)
Recently, scholars and practitioners around the globe have started to view decentralization as an integral part of broader health reforms. Nevertheless, the literature on decentralization has tended toward case studies and theoretical discussions rather than rigorous empirical analysis, and few quantitative studies have explored the practical consequences of decentralization of health service delivery. This study attempts to address this issue by exploring the impact of decentralization on health outcomes with a panel dataset of 22 countries from 1990 to 2005. Our findings indicate healthcare decentralization is nonlinearly beneficial to improve the health of a population. The effect of decentralization on population health remains positive within a certain threshold, but becomes negative beyond the transition point. Considering the institutional background of healthcare, the institutional setting of reliance on market mechanisms in service provision and on private insurance for basic coverage is a precondition for decentralization reform to further create a positive impact.